PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING TIPE TANDUR TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA - Ikasmayanti Ikasmayanti; Sukainil Ahzan; Wirawan Putrayadi (Lensa: Jurnal Kependidikan Fisika, 2015)
This purpose of this reseach was to measure the effect of Quantum Teaching model of TANDUR toward creative thinking ability of student. This research was conducted in the class VIII SMPN 3 Madapangga. The population of this study was all students grade VIII, and got two class as sample were VIIIa and VIIIb. Students at VIIIa as experimental and VIIIb as control class. This research was experimental reseach with post test only control group design. This study using purposive sampling. The instrument in this research was test of creative thinking was formed essay test. Data analysis in this study using t-test. From the treatment was obtaimed creative thinking ability with tcalc = 1,71 ≥ ttab = 1,68. This the null Hypotesis (Ho) in push away and alternative Hypotesis (Ha) in acceptance. From data analysis can concluded that Quantum Teaching type TANDUR can increase the creative thinking ability of students at vibration items and wave.